Draft amendments to Articles V and VII of the Constitution and related proposals aimed at improving the efficiency of the work of the Executive Board; item proposed by Japan - UNESCO. General Conference, 26th session, 1991 (1991)
Document containing the draft resolution submitted by Japan concerning amendments to Articles V and VII of the Constitution and related proposals aimed at improving the efficiency of the work of the Executive Board, it also contains the modifications that various Member States propose to make to this draft resolution